Strategies for the improvement of agricultural extension work and non-degree agricultural training in Nigeria - Kincaid, James M. (East Lansing, Michigan : Consortium for the Study of Nigerian Rural Development, Michigan State University], 1968)
This report summarizes two years of continuous research about agricultural extension and non-degree agricultural education and training in Nigeria. It is largely a compilation of the findings and conclusions of several general and specific studies conducted by the Sub-project 2 research group during 1966-68.
"Report by CSNRD/Subproject 2 'Nonuniversity and extension training in agriculture.'"
Includes bibliographical references: p. 145-147.
ne 05/11/2019
Loans
Keywords: Agricultural extension work; Nigeria